Mineral status in canine medial coronoid process disease: a cohort study using analysis of hair by mass spectrometry - Davies, M.; West, J.; Williams, C.; Gardner, David S. (BMJ Publishing Group, 2017)
In several species, developmental skeletal diseases involving abnormal endochondral ossification have been associated with imbalanced mineral intake. Hair analysis reflects long-term mineral status. To determine the mineral content of hair from dogs with or without medial coronoid process disease (MCPD). Dogs with MCPD have a different profile of minerals known to influence metalloenzymes involved in endochondral ossification. After cleansing, chelation and acid digestion of hair samples (n=79 in total: control dogs, n=70 v MCPD, n=9), mineral profile (7 major and 25 trace elements) was determined by inductively coupled plasma-mass spectrometry. Dogs were of similar age (control, 4.05 [1.85-7.70] v MCPD, 4.30 [3.25-6.53] median (IQR) years; P=0.78) and gender (control, n=43/27 v MCPD, n=4/5 males/females). 28/70 (40 per cent) of control and 8/9 (88 per cent) of MCPD dogs were neutered, respectively. Hair from dogs with MCPD contained significantly lower amounts (µg/g/DM) of copper, sulphur and zinc (all at P<0.001). Age, sex and neutered status had no effect on hair mineral status. Based on hair analysis, a role for mineral imbalance including copper, sulphur and zinc in the aetiopathogenesis of canine MCPD is suggested. Hair mineral analysis may prove useful as a biomarker for susceptible puppies.